Characterization of single crystalline austenitic stainless steel thin struts processed by laser powder bed fusion. (1st April 2019) - Wang, X.; Muñiz-Lerma, J.A.; Sanchez-Mata, O.; Attarian Shandiz, M.; Brodusch, N.; Gauvin, R.; Brochu, M.
Abstract: Single crystalline austenitic stainless steel struts with a diameter of 250 μm were successfully fabricated using laser powder bed fusion (LPBF). The struts exhibited a strong 〈110〉 texture parallel to the building direction (BD). Excellent strength-ductility combination was achieved for the struts, which is attributed to the strengthening of the fine cellular sub-grains and the twinning-induce plasticity (TWIP) effect. After deformation, dynamic recrystallization (DRX) was observed and its presence is closely related to the unique microstructure of the single crystalline struts. Graphical abstract: Unlabelled Image